THE INTONATION OF CONDITIONAL AND INTERROGATIVE PROMISES IN JORDANIAN ARABIC - Khalid Alsmadi; Kamariah Yunus; Yasmeen Almadani, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study aimed at investigating the intonation of interrogative and conditional utterances used to perform a promising speech act in Jordanian Arabic through analysing the utterances involved acoustically. Actually, it attempted to figure out the interrogative and conditional constructions carried out in the performance of a promising speech act along with the accompanying intonational patterns. The study data were composed of a definite number of recorded utterances by five Jordanian Arabic native speakers. The data were analyzed using “PRAAT software” (version No. 5304). Focusing on the measurements of the F0 (pitch), the results indicated that a promising speech act would be performed using the first conditional, second conditional (fals promise), formal wh-question and informal wh-question used along with tones such as the high-fall, low-fall, and rise-fall tunes.